Amelia Bedelia and the surprise shower - Parish, Peggy; Thomas, Barbara Siebel; Siebel, Fritz (New York : HarperCollins, 1995)
While helping to prepare a surprise shower, Amelia Bedelia and her cousin make some arrangements that are not quite what the guests expected.
71279
Keywords: Amelia-Bedelia (Fictitious character) -- Juvenile fiction; Showers (Parties) -- Juvenile fiction; Parties -- Fiction; Humorous stories; EZ; Humorous stories